A Case Study on Petronas Globalization a Strategic Management Decision - Hussain, Ahmad (1999)
PETRONAS vision was "To be A Leading Oil and Gas Multinational Company of Choice" and it stated the globalization effort in 1994. PETRONAS global operation had extended to Africa countries, Confederate Independence of Soviet Union (CIS), Middle East and Asia Pacific countries. Some of the Africa countries included Sudan, South Africa (downstream Engen), Libya and Algeria. The investments in CIS were Turkmenistan and Kazarkstan. The investment in Middle East countries included Iran, Syria and Iraq. In the Asia Pacific, the oversea portfolios extended to Vietnam, Mynmar, China and Australia (both Upstream and downstream). The oversea upstream activities were undertaken by its subsidiary PETRONAS Carigali Sdn Bhd (PCSB) through its oversea subsidiary companies. When PETRONAS started its globalization efforts, the environmental factors were very much favorable. However, in 1 997 and 1998 there were adverse changed in these environmental factors and had affected PETRONAS globalization efforts. Some of these factors were the regional and world economic turmoil, regional financial and currency devaluation, slower economic growth, low demand of oil and gas, lower oil and gas price and lower prospectivity and commerciality of the oil and gas projects. This case study evaluated PETRONAS strategic position and the impact on the international portfolios and made recommendation relating to these strategic issues. This case study analyzed the environmental factors influencing the company future direction through the used of the SWOT analysis and determined the strategic thrust to comprehend the SWOT analysis. This study assessed analytically, through the used of SPACE, the future company direction and evaluated the oversea portfolios to determine the portfolios growth opportunities and provide the decision as to whether these portfolios should be retained, partnered or divested.